TEACHING PRONUNCIATION BY WRITING PHONETIC SYMBOLS FOR PRONUNCIATION 1 CLASS (A CASE STUDY AT THE EMINENCE ENGLISH COURSE) - Priyanto, Agung (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2020)
The aim of this study is to describe the process of teaching pronunciation by writing phonetic symbols at The Eminence English Course Pare. Those are including of: the process of teaching pronunciation by writing phonetic symbols at The Eminence, the students’ response toward the process of teaching pronunciation, and tutor solution of the problems which are faced by students. Qualitative was selected as a research approach; observation was used to collect some information about pronunciation program. The instrument used for collecting documents which is related to pronunciation program was documentation, it was kind of module book. The questionnaire was used to get students’ perception in teaching learning process at pronunciation program. The result of this study showed that the process of teaching phonetic symbols at The Eminence had been supported by syllabus and lesson plan although it was not written yet structurally, the material was taken from module book, the media is using whiteboard, speaker, and Oxford dictionary. The method which was used was direct or natural method, the technique which was applied in the class was reading aloud technique. The evaluation of this program was taken on Sunday at the second week by giving written test. From the result about the students’ perception was known that students had problems in pronunciation. It is word connection. Tutor solves this problem by giving word connection material.